A buccaneer at heart - Laurens, Stephanie (Laurens, Stephanie. Adventurers quartet, 2016)
Wanting to settle down after a decade of captaining diplomatic and covert missions for the crown, Captain Robert Frobisher takes a final assignment in West Africa gathering information against a slaver camp, where he falls for a woman trying to find and rescue her missing brother. --Publisher.